An application of Neutrosophic fuzzy simple additive weighting method in higher education selection / Nur Daliena Mohd Razif - Mohd Razif, Nur Daliena (2023)
A university is a higher education institution that provides undergraduate and graduate programmes leading to academic and professional degrees. Malaysia's public and private universities are both growing in number. Choosing the appropriate university may make or break a person's future career and life chances. The Neutrosophic fuzzy simple additive weighting (NFSAW) approach will be used to evaluate which university is the finest in Malaysia. The method involves finding the truth, indeterminacy, and false membership rating values for each criterion. It also involves determining the average fuzzy score and defuzzified score of each alternative on each criterion. This study uses data from questionnaires that distributed to the experts. The main objectives of the study are to identify the factors that influence higher education selection among secondary school students, and to calculate the weight for each factor in choosing between university and non-university options. The study also aims to rank the best alternative of university using the NFSAW method. Through this study, we can learn more about the NFSAW approach and how to use it. Moreover, this research will help to ease the students to find which the best university in Malaysia.